Heterotopic Gastric Mucosa in Cervical Oesophagus: Clinical Observations - A. I. Dolgushina; A. O. Khikhlova; E. R. Olevskya; O. V. Naumenko; S. Yu. Belousov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2021)
Aim. Description of the endoscopic and clinical traits of heterotopic gastric mucosa (HGM) observed in cervical oesophagus.Key points. HGM in proximal oesophagus can be asymptomatic or have various clinical manifestations. A 40-yo female patient consulted a gastroenterologist with complaints of cough and globus sensation. For several years she was visiting an otorhinolaryngologist and psychotherapist, with therapy ineffective. Esophagogastroduodenoscopy (EGDS) at the last visit revealed several foci of HGM in cervical oesophagus of 1.2 x 0.8 cm maximal size. The patient was prescribed a combined prokinetic — proton pump inhibitor therapy, which relieved the symptoms. EGDS in a 21-yo patient without active complaints revealed a 2 cm-wide HGM of 4/5 cervical oesophageal lining with acidproducing zones.Conclusion. Two different scenarios of cervical oesophageal HGM are described, the first one manifested with laryngopharyngeal reflux, and the second devoid of clinical manifestations despite a large heterotopic site.